Trends in HPV vaccination initiation and completion among U.S. adolescents aged 13–17 years, 2021–2023: Findings from the National Immunization Survey–Teen - Taylor Mullin; Jesse Plascak; Alai Tan; Jodi Ford; Henry Duah; Diane Von Ah (PLoS ONE, 2026)
Human papillomavirus (HPV) vaccination is a key strategy for preventing HPV-related cancers, yet series completion among U.S. adolescents remains below national public health goals. This study analyzed nationally representative data from the 2021–2023 National Immunization Survey–Teen (NIS-Teen) to describe recent patterns in HPV vaccination initiation and completion among adolescents aged 13–17 years. Complex survey–weighted analyses estimated the proportion of adolescents who had not initiated HPV vaccination, had initiated but not completed the series, or had completed the series based on provider-verified vaccination records and Advisory Committee on Immunization Practices (ACIP) age-specific dose recommendations. The analytic sample included 126,226 adolescents. Weighted estimates indicated that 39.8% were aged 13–14 years and 60.2% were aged 15–17 years; 51.2% were male and 48.8% female. HPV vaccine series completion remained stable across survey years, with completion estimates of 62.4% in 2021, 63.9% in 2022, and 62.5% in 2023. Initiation without completion ranged from 14.4% to 15.2%, while non-initiation ranged from 21.7% to 22.9%. Across all years, completion was consistently higher among older adolescents and females compared with younger adolescents and males. Despite modest gains in initiation, HPV vaccination coverage remained relatively stable during the study period. This stability, observed during the COVID-19 recovery period, may reflect preservation of uptake rather than true stagnation. These findings highlight the need for strategies emphasizing early vaccination, strong provider recommendations, and reminder-based follow-up to improve series completion and advance national immunization targets.